Crowd-based open innovation in telco operators: readiness assessment for smart city service development - Sarić, Željko; Obradović, Vladimir; Bogdanović, Zorica; Labus, Aleksandra; Mitrović, Svetlana (Serbian Journal of Management, 2022)
This paper studies the readiness of the Serbian telco operators and other stakeholders to implement a crowd-based open innovation business model. Telco companies are facing challenges in terms of market demands and with finding new opportunities to attract subscribers with innovative products and services. These innovations are frequently oriented towards smart city services based on emerging technologies such as Internet of things, cloud computing, software defined networks and blockchain. Due to complexity, pace and costs of research and development, telco operators have already recognized the need to shift from a traditional to an open innovation concept. The development of crowdsourcing models has further fueled the possibility to include customers in the open innovation process, in order to better design and develop services suited to their own needs. With this in mind, the goal of this paper is to propose a crowd-based open innovation business model for improvement of innovation capacities of Serbian telco operators. The proposed model is used as the basis of evaluating the readiness of internal and external stakeholders for participation in open innovation projects. The study is based on the adjusted value-based adoption model, while the analysis is performed using the PLS-SEM method. The results show that participants identify trust as the most influential factor for the perceived value of crowd-based open innovation, while the internal stakeholders of telco companies find expected income and reputation as the most relevant. Both groups have shown a high interest in innovations related to smart city services such as smart traffic and ecology-related services.